CLASS STRUGGLE IN 1984 BY GEORGE ORWELL - Mandai, Disyela Apriswa; Astuti, Rengganis Elung Naafi; Ekayani, Ridha; Nurholis, Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
This article researches the complicated class structure of George Orwell's dystopian masterpiece, which is the novel titled